New Hypotheses and Unanswered Questions in Running Injury Research - comment on Nigg et al. - James Becker (Bern Open Publishing, 2018)
After critical evaluation of the evidence, Nigg et al.'s target article reject currently discussed hypotheses regarding relationships between impact forces, pronation, and running injuries.  In doing so, they highlight methodological questions underlying research in this field.  This commentary focuses on three such questions including: how are impact forces and the relationship between impact and injury being quantified, what are the methods currently used to measure foot pronation and what are metrics being extracted, and the importance of focusing on individual response patterns.   Each of these areas represents important venues for continued development in the field of running biomechanics and running injuries.